Pengembangan Modul Elektronik Menulis Teks Cerpen Berbasis Project Based Learning bagi Siswa Kelas XI SMA - Khairalfi Jumanisa Amril; Harris Effendi Thahar (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2022)
This study aims to describe the process of developing an electronic module for learning to write short stories based on project-based learning that is valid, practical, and effective, which class XI high school students use. This research and development (R&D) use a 4D development model, which includes definition, design, development, and deployment. The results of this study indicate that the electronic module improves student learning outcomes. It is evidenced by the results of the electronic module's validity, practicality, and effectiveness. The validity of the electronic module by experts is 95.1%, so the electronic module is categorized as very valid. The practicality of the electronic module by the teacher is 93.05% in the very practical category, and the practicality by students is 85.8% in the very practical category. Student learning activities are 97.5% in the very active category. The effectiveness of the electronic module is based on the results of the student knowledge test, the average score obtained is 87 with an A predicate. Based on the student skills test results, the average score obtained is 87 with an A predicate (very effective).